2019
DOI: 10.1002/jctb.5881
|View full text |Cite
|
Sign up to set email alerts
|

Attapulgite‐supported magnetic dual acid–base catalyst for the catalytic conversion of lignin to phenolic monomers

Abstract: BACKGROUND Research on the catalytic conversion of lignin into value‐added chemicals has grown rapidly on account of the importance of lignin in the biorefinery. There is thus a need to investigate novel technologies to depolymerize lignin in the absence of hydrogen gas and noble metal catalysts. This study developed a cheap and recyclable catalyst via a facile process involving impregnation and calcination for the conversion of lignin to value‐added phenolic monomers. RESULTS Acid sites, basic sites and magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(90 reference statements)
2
1
0
Order By: Relevance
“…On the other hand, ATP presents a higher population of medium and strong basic sites. The profiles received in this study are in good agreement with the ones that were reported by Wu et al [43]. of both Cao and MgO, which can explain the dolomite structure detected herein.…”
Section: Glycerol Steam Reformingsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, ATP presents a higher population of medium and strong basic sites. The profiles received in this study are in good agreement with the ones that were reported by Wu et al [43]. of both Cao and MgO, which can explain the dolomite structure detected herein.…”
Section: Glycerol Steam Reformingsupporting
confidence: 93%
“…On the other hand, ATP presents a higher population of medium and strong basic sites. The profiles received in this study are in good agreement with the ones that were reported by Wu et al [43]. Ni/ATP presents a wide distribution of weak, medium, and strong acid sites, as indicated by the peaks at 150, 300, 400, and >500 • C. Similarly, Ni/Al catalyst exhibits a polydispersity of acid sites strength, with a much lower population though.…”
Section: Glycerol Steam Reformingsupporting
confidence: 91%
“…Then, the oxygen-containing functional groups in lignin interacted with oxygen vacancies and zinc particles on the catalyst surface . The lignin adsorbed on the catalyst surface was activated by acidic sites and catalyzed by nickel to yield enol ether intermediates by the protonation of −OH in lignin . The intermediates were further depolymerized to generate monophenolic compounds, while a portion of the intermediates containing benzyl cations might be attacked by other aromatic nuclei during the reaction process, resulting in a condensation reaction.…”
Section: Resultsmentioning
confidence: 99%